2021
DOI: 10.1177/2333721421997620
|View full text |Cite
|
Sign up to set email alerts
|

Unwelcome Companions: Loneliness Associates with the Cluster of Pain, Fatigue, and Depression in Older Adults

Abstract: Objective: Pain, fatigue, and depression commonly co-occur as a symptom cluster in pathological inflammatory states. Psychosocial stressors such as loneliness may lead to similar states through shared mechanisms. We investigated the association of loneliness with pain, fatigue, and depression in older adults. Methods: Using Health and Retirement Study data ( N = 11,766), we measured cross-sectional prevalence of frequent, moderate to severe pain; severe fatigue; depressive symptoms; and co-occurrence of sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 58 publications
(90 reference statements)
3
18
0
Order By: Relevance
“…These results were consistent with previous studies which investigated the negative effects of loneliness and social isolation with pain 10 , 11 , 13 , 14 . However, the association between social isolation and a higher risk of pain was partly contrary to a previous study that reported that people who experienced chronic musculoskeletal pain had a higher risk of loneliness but had a lower risk of being socially isolated 12 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were consistent with previous studies which investigated the negative effects of loneliness and social isolation with pain 10 , 11 , 13 , 14 . However, the association between social isolation and a higher risk of pain was partly contrary to a previous study that reported that people who experienced chronic musculoskeletal pain had a higher risk of loneliness but had a lower risk of being socially isolated 12 .…”
Section: Discussionsupporting
confidence: 93%
“…A previous epidemiological study using data from the English Longitudinal Study of Ageing (ELSA) cohort reported that loneliness was associated with the higher prevalence of musculoskeletal pain 12 . Other studies demonstrated that loneliness is strongly associated with pain 10 , 13 , 14 , and social isolation predicted pain interference 11 . Therefore, a worsening of psychological stress due to the increased loneliness and social isolation experienced during the COVID-19 pandemic may contribute to the onset of pain 15 .…”
Section: Introductionmentioning
confidence: 93%
“…The English Longitudinal Study of Ageing (ELSA) epidemiological study established that loneliness leads to higher prevalence of musculoskeletal pain [ 35 ]. In accordance, other studies showed that loneliness is strongly associated with pain exacerbation [ 33 , 36 , 37 ] and that social isolation is likely to amplify the perception of pain [ 34 ]. Therefore, the psychological stress and the physical isolation due to COVID-19 pandemic surely contributed to the onset of pain [ 38 ] and had a large impact on patients with chronic back pain and low tolerance to psychological stress [ 38 40 ].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, women tend to live longer than men. Living without a spouse can shrink a women’s family networks, which may then reduce the impact of family networks on loneliness among women [ 44 , 45 ]. In our analyses, the contribution to the variance of health variables was equally strong for loneliness in both men and women, and was around 35%.…”
Section: Discussionmentioning
confidence: 99%